The Correlation Between Midwives' Knowledge And Early Stunting Detection Through Implementation Of Congenital Hypothyroidism Screening In Infants At The Inpatient Ward Of Rd Dkt Hospital, Kediri City - Lailaturohmah Lailaturohmah; Weni Guslia Refti (CV. AFDIFAL MAJU BERKAH, 2026)
This study aims to analyze the relationship between the knowledge level of midwives and the implementation of early stunting detection through Congenital Hypothyroidism Screening (CHS) in infants at RS DKT Kota Kediri. Stunting remains a major public health problem in Indonesia due to its long-term impact on physical growth, cognitive development, and susceptibility to chronic diseases. Congenital hypothyroidism is a preventable risk factor for stunting when detected and managed early; however, the coverage and consistency of CHS implementation in healthcare facilities are still limited and highly dependent on healthcare workers’ competence. This study employed a quantitative approach with a cross-sectional design. The respondents consisted of 26 midwives working in inpatient wards and polyclinics at RS DKT Kota Kediri, selected using total sampling. Data were collected using a structured questionnaire to assess midwives’ knowledge regarding CHS and an observation checklist to evaluate the implementation of CHS based on established Standard Operating Procedures (SOP). Data analysis was conducted using the Chi-Square test to examine the relationship between knowledge level and CHS implementation. The results showed that the majority of respondents had good knowledge regarding congenital hypothyroidism screening, and most midwives implemented CHS in accordance with SOP. Statistical analysis demonstrated a significant relationship between the knowledge level of midwives and the proper implementation of CHS (p < 0.05), indicating that higher knowledge levels were associated with better compliance with screening procedures. This study highlights the critical role of midwives’ knowledge in ensuring the effective implementation of congenital hypothyroidism screening as an early detection strategy for stunting risk. Strengthening continuous education, targeted training programs, and institutional support for CHS implementation are essential to improve screening coverage and contribute to comprehensive stunting prevention efforts in hospital settings